Comparative Study on Chemically and Biologically Raised Crackers Biscuits - Rahman, MS; Siddiqui, AA; Matin, A (Journal of Environmental Science and Natural Resources, 2015)
The experiment was conducted to the comparative study of chemically and biologically raised cracker biscuit. There were two different formulas; Formula -A was biologically raised (using dry yeast) and Formula B was chemically raised (using sodium bicarbonate, no yeast) crackers. For analyzing the quality of products, samples were collected from different points of the plant and conducted physical, chemical and organoleptic test. From physical test report it is found that the appearance, texture, color and flavor are better for formulation A than the formulation B. According to chemical test report it are found that oven moisture, Packing moisture, Fat and Ash were 1.9%, 2.8%,24.0% and 0.93% respectively of formulation A and 2.0%, 3.1%, 24.2% and 0.92% respectively for formulation B. From the panel test report 66.66% group voted the formula A and 33.33% group voted the formula B by the team -1 and secondly we form teamed 2 by rearranging the team members of one and two. According to team-2 83.33% group voted the formula A and 16.66% group voted the formula B. All the test reports supported that biologically raised crackers biscuits was better than the chemically raised crackers biscuits. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22103 J. Environ. Sci. & Natural Resources, 6(2): 97-100 2013